Sport and public policy social, political, and economic perspectives - Mildner, Gerard C. S.; Santo, Charles Andrew (Champaign, IL Human Kinetics, 2010)
Sports figures, events, and organizations affect our society in vast, varied, and sometimes unexpected ways. To gain a broad-based understanding of how sport interfaces with public policy issues, a variety of viewpoints must be considered. Sport and Public Policy: Social, Political, and Economic Perspectives is the only text that examines some of the most compelling policy issues affecting the sports world from an interdisciplinary perspective--including economics, history, urban planning, not-for-profit administration, public health communications, political science, and philosophy. With contributions from a wide range of scholarly disciplines, this contemporary resource enhances traditional conversation and gives readers a fresh outlook on economic and political issues in sport. Sport and Public Policy presents a contemporary view of how to understand and analyze complex and controversial topics. It begins by examining issues related to professional sports--including the unique nature of American sports leagues, the decisions and conflicts involved in the organization of sports leagues and events, and labor strikes and conflicts. It then examines professional sports, cities, and public finance. Readers are drawn into thought-provoking discussion of issues such as the public investment in sports facilities and recent trends in stadium and arena construction. The book also presents an example of a unique model of not-for-profit community ownership in action, which readers can implement in their own cities. Sport and Public Policy explores amateur sports by presenting a fresh perspective on the link between sports and society, the dwindling levels of African-American participation in baseball, and whether or not the National Collegiate Athletic Association's actions align with its stated principles and values. It also challenges the reader to think globally through a discussion of how sports affect and are affected by international relations, how a changing world economy is affecting the Olympic games, Major League Baseball's efforts at global expansion, and the effects of global consumer marketing efforts. The chapters encourage readers to consider their role as participants in sports and use their great power to make individual choices that influence their communities. To enhance the learning experience, Sport and Public Policy offers the following: An application and implementation section in select chapters helps readers understand how to apply the content in their own roles in the sport industry or society. The case studies added to most chapters illustrate how the information and research are being applied in the real world. Some of the hottest topics in the sports world are covered from a public policy perspective, giving readers a new angle from which to analyze issues now and in the future. Sport and Public Policy is a timely resource that will be valued by many. Researchers will use it as a springboard for further study of how sport affects our society economically, socially, and politically. Practitioners and anyone else interested in the role of sport in America will find the book creates a critical new awareness of sport's interface with public policy and the potentially far-reaching implications of their decisions.
Part I. The Structure of Professional Sports -- Chapter 1.Cooperation Amidst Competition: The Nature of Sport Leagues / Nathaniel Sampson and Gerard C.S. Mildner ; Why League Cooperation Is Necessary ; Downside of Cooperation ; Organized Baseball: Evolution of a Cartel ; Antitrust Law Interpretations and Baseball ; Antitrust and Other Leagues: Are All Sports Equal? ; Effect of Public Policy on the Balance of Power ; Future Trends ; Conclusion -- Chapter 2. Beyond the Major Leagues: Lessons from the Organization of International Sports / Gerard C.S. Mildner ; Organization of Soccer, the World Sport ; Women's Soccer: The Trial of a Single-Entity League ; Rugby: The Contest over Professionalism, Nations, and Clubs ; Cricket: The Broadcaster's Leagues ; Lessons for American Sports ; Future Trends ; Conclusion -- Chapter 3. Why Professional Athletes Make So Much Money / Zenon X. Zygmont ; The NHL's Missing Season ; Wage Determination in Professional Sports ; Free Agency ; Evaluating Player Productivity ; Is it Possible to Pay too Much? ; Future Trends ; Conclusion -- Part II. Professional Sports, Cities, and Public Finance -- Chapter 4. Economic Impact of Sport Stadiums, Teams and Events / Charles A. Santo ; Public Cost of Big-Time Sports ; Economic Magnitude of Sports in Perspective ; Promoting Sport Investment Through Economic Impact Analysis ; Sources of Exaggeration in Economic Impact Analysis ; Ex Post Facto Empirical Evaluations ; Policy Implications on Predicted Economic Impacts ; Conclusion -- Chapter 5. Cities, Stadiums, and Subsidies: Why Cities Spend So Much on Sports / Charles A. Santo ; Evolution of Major League Sport Facility Development ; Political Economy of Sport Facility Development ; Importance of Consumption Benefits ; Future Trends ; Conclusion -- Chapter 6. Community Ownership of Professional Sport Teams and the Role of Social Entrepreneurship / Dorothy Norris-Tirrell and Susan Tomlinson Schmidt ; Identifying Community Ownership Alternatives ; Using the Nonprofit-Charitable Purpose Structure: The Memphis Redbirds Baseball ; Foundation ; Future Trends ; Conclusion -- Part III. Amateur Athletics, Participation, and Public Health -- Chapter 7. Influences of Urban Form on Physical Activity / Jennifer Dill and Lynn Weigand ; Importance and Decline of Physical Activity in the United States ; How Urban Growth Has Made Us Less Active ; Public Policies to Increase Physical Activity ; Do These Strategies Work? ; Future Trends ; Conclusion -- Chapter 8. MLB's Mixed Messages: African American Participation in Baseball / David C. Ogden ; Myth and Semiotics ; Analyzing MLB's Messages ; Moving from Political Speech to Myth ; Challenging Myth ; Policy Implications for Myth Making ; Future Trends ; Conclusion -- Chapter 9.Contradictions and Conflicts: Ethical Dilemmas Inherent in Big-Time College Sports / Richard Southall, Mark S. Nagel, John Amis,and Crystal Southall ; College Sports Today ; National Collegiate Athletic Association (NCAA) ; Corporatization in College Sports ; Institutional Logics ; Case Study: 2006 NCAA Men's Basketball Tournament Broadcasts ; Future Trends ; Conclusion -- Chapter 10. Sport, Doping, and Public Policy / Bryan E. Denham ; Mediated Doping Representations and the Formation of Public Policy ; Sporting Competition and the Formation of Regulatory Bodies ; Media Representations, Government Hearings, and Public Policy in the 21st Century ; Future Trends ; Conclusion -- Part IV. Sports and Globalization -- Chapter 11. Political Economy of the Olympic Games / Gregory Andranovich, Matthew J. Burbank, and Charles H. Heying ; Globalization, the New Economy, and Political Economy ; Political Economy and the Olympic Games ; Los Angeles: The Market Matters Most ; Atlanta: The State Matters Most ; Mexico City: Civil Society Matters Most ; Future Trends ; Conclusion -- Chapter 12. American Baseball and the Global Labor Market: Resistance and Hegemony in the Caribbean / Charles A. Santo ; Globalization of American Professional Baseball ; Shared History and Parallel Development of Caribbean Baseball ; Dominican Dependency, Underdevelopment, and Exploitation ; Cuban Nationalism and Resistance ; Movement Along the Spectrum ; Future Trends ; Conclusion -- Chapter 13. Expanding Global Consumer Market for American Sports: The World Baseball Classic / Mark S. Nagel, Matt T. Brown, Dan A. Rascher, and Chad D. McEvoy ; Baseball's Worldwide Development ; The Consumption of MLB in the United States ; The Creation of the World Baseball Classic ; World Baseball Classic Revenue Sources ; Future Trends ; Conclusion.
Includes bibliographical references
Keywords: Sports -- Economic aspects; Sports -- Social aspects